Device for transosseous osteosynthesis at thefractures of the clave - Bodnya, A.; Butenko, L.; Vadatursky, M. (Journal of Education, Health and Sport, 2023)
The article presents a technical solution to the issues of external osteosynthesis in the treatment of clavicle fractures, which is mainly characterized by insufficient capabilities inherent in the structures to move fragments in different directions and planes. Purpose: to establish the distinctive features of the known external devices used in the osteosynthesis of clavicle fractures, and to develop a design taking into account the identified shortcomings. Material and methods: based on the identified shortcomings in various author's designs, an original device was developed for the treatment of patients with fractures of the considered localization. The use of the device involves the use of stabilizing and repositioning screw rods, which are inserted through the proximal and distal fragments of the clavicle. A feature of the introduction of these screw rods is that they are located relative to each other at an angle of 90°, which ensures stable fixation of fragments of the clavicle in all planes. The method of rod fixation developed in the clinic allows for controlled reposition using repositioning nodes, the mobility of which is possible in three planes. Stable fixation of fragments of the clavicle is maintained until the fracture heals, while ensuring the function of the shoulder and elbow joints. Conclusions: evaluation of the technical results of the device showed that external osteosynthesis can be the method of choice for treatment and have practical application in trauma departments.